Can the UroLift prostatic implant device treat the symptoms of benign prostatic hypertrophy, avoid sexual dysfunction and reduce hospital TURP waiting times? A single centre, single surgeon experience and review of the literature. (3rd July 2017) - Bardoli, Antonio D.; Taylor, Will St J.; Mahmalji, Wasim
Abstract: BPH associated with LUTS and sexual dysfunction is common. We performed UroLift on 11 patients, average age 71 years (range 56–90). IPSS improved by an average of 9 points post-procedure. Pre-operatively their post-void residuals were 306.3 ml (range 120–499 ml SD [120.6]) and their QMAX was 7 ml/s (range 4–14 SD [2.8] ml/s). Post-procedure the post-void residual decreased by 35.4% at 4 months (mean difference – 106.3 ml). QMAX improved by an average of 1.7 ml/s, which was not statistically significant. No patients suffered any sexual dysfunction side effects and all patients were satisfied with their result. Hospital stay and theatre time were significantly reduced. Average length of stay was just 10.6 (6–18) hours and average theatre time just 18.7 (12–30) min. This is significantly faster than other surgery for LUTS. We therefore feel that there are significant benefits for both the patients, who are able to go home much faster, and also the hospital, who are able to perform far more surgeries for their patients. Patients also do not require an inpatient bed so patients should not be cancelled on the day of theatre.